REKONSTRUKSI HUKUM PIDANA MATERIIL PADA KORPORASI DALAM TINDAK PIDANA PERPAJAKAN DI INDONESIA - Bambang Bambang Ali; Supriyanta Supriyanta (RESEARCH FAIR UNISRI, 2023)
Subjects of Tax Law are individuals and Legal Entities or Corporations. In enforcing tax law, tax law violations often occur, both by individuals and corporations. Efforts to resolve this deviation for individual perpetrators are easier to resolve in accordance with applicable law, but for corporate perpetrators material criminal law experiences problems. For perpetrators (corporations or legal entities) of tax crimes to be given criminal penalties or sanctions, the material criminal law must be changed or reconstructed. To reconstruct this, research needs to be done. The research was conducted through normative juridical research, which is based on secondary data. The nature of the research is descriptive research. The dominant data source is secondary data, which includes primary legal materials, secondary legal materials and tertiary legal materials. The results of the research show that if the material criminal law that regulates criminal acts in the field of taxation in its sanctions is not changed or reconstructed, then legal entities or corporations as perpetrators of criminal acts cannot be charged with the material criminal law contained in Law no. 28 of 2007 concerning General Provisions and Tax Procedures. Keywords: Reconstruction, material criminal law, corporations.